2003
DOI: 10.1159/000073764
|View full text |Cite
|
Sign up to set email alerts
|

Aging Effects of Sympathetic Reflex Activities on Skin Nerves

Abstract: Background: Muscle sympathetic nerve activity (MSNA) at rest is widely known to increase with aging, but changes in skin sympathetic nerve activity (SSNA) with aging are less well defined. We examined the aging effects of reflex activities on SSNA, sympathetic skin response (SSR), and sympathetic flow response (SFR). Objective: We studied the aging effect of reflex activities on SSNA, SSR and SFR. Methods: SSNA, SSR and SFR were simultaneously recorded during randomly administered electrical stimuli. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…We measured the SSR at the upper extremities, because these responses have been shown to be more reliable than those of the lower extremities, particularly in the elderly (Drory and Korczyn, 1993;Watanabe et al, 2003). We measured the SSR at the upper extremities, because these responses have been shown to be more reliable than those of the lower extremities, particularly in the elderly (Drory and Korczyn, 1993;Watanabe et al, 2003).…”
Section: Sympathetic Skin Response (Ssr)mentioning
confidence: 99%
See 1 more Smart Citation
“…We measured the SSR at the upper extremities, because these responses have been shown to be more reliable than those of the lower extremities, particularly in the elderly (Drory and Korczyn, 1993;Watanabe et al, 2003). We measured the SSR at the upper extremities, because these responses have been shown to be more reliable than those of the lower extremities, particularly in the elderly (Drory and Korczyn, 1993;Watanabe et al, 2003).…”
Section: Sympathetic Skin Response (Ssr)mentioning
confidence: 99%
“…For recording the differential surface electrode was fixed at the palm of the left hand with the reference electrode fixed on the proximal third of the left forearm. We measured the SSR at the upper extremities, because these responses have been shown to be more reliable than those of the lower extremities, particularly in the elderly (Drory and Korczyn, 1993;Watanabe et al, 2003). Amplitude and latency of the SSR were measured.…”
Section: Sympathetic Skin Response (Ssr)mentioning
confidence: 99%
“…We measured the SSR at the upper extremities, because these responses have been shown to be more reliable than those of the lower extremities, particularly in the elderly [23,24] . Amplitude and latency of the SSR were measured.…”
Section: Autonomic Responsesmentioning
confidence: 99%
“…There were no differences in electrical stimuliinduced reflex skin sympathetic nerve activity between young and older subjects, but effector organ responses such as SSR were diminished in older subjects [33]. Karatas et al [20] revealed that there was a negative correlation with age and RR interval and trained sportsmen (n = 22).…”
Section: Discussionmentioning
confidence: 95%